Hidden Motivation for Knowledge Sharing Behavior and Organizational Recognition: The Moderating Role of Need for Status - Li, Zhao; Kumar, Shalendra S; Kishore, Rohit; Krishna, Bimal; Lingam, Shiu (Humanities and Social Sciences Letters, 2020)
This study aims to examine the relationship between the hidden motives for sharing knowledge, organizational recognition and the moderating role of the need for status. The survey data was collected from 798 employees through convenient sampling from public sector organizations in Fiji. The findings revealed that the need for status significantly moderated the relationship between hidden motives to share knowledge and organizational recognition. In congruence with the costly signaling theory (CST), the study identified an underlying motive that can motivate individuals to proactively engage in sharing valued resources to gain social prestige and self-recognition. The findings also revealed that by sharing highly valued resources individuals maintained social status and at the same time earned preferential treatment in the organization. As such, this became our major contribution to the existing literature on knowledge management. Finally, this study brings a new dimension to unleashing the hidden motivation of knowledge sharing behavior through the individual need for status and the real benefit of managing individuals in an organization. Organizations can effectively create a work context that would encourage more proactive knowledge sharing behavior and also set a platform for the fulfillment of the individual need for status. Moreover, it becomes the responsibility of leaders to elicit belief in individuals that efforts made to share knowledge is highly valuable and distinguishable, and any cost incurred will not be wasted. The limitations and suggestions for further research are also discussed.